2010
DOI: 10.1093/jxb/erq012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of actin dynamics by actin-binding proteins in pollen

Abstract: A dynamic network of polymers, the actin cytoskeleton, co-ordinates numerous fundamental cellular processes. In pollen tubes, organelle movements and cytoplasmic streaming, organization of the tip zone, vesicle trafficking, and tip growth have all been linked to actin-based function. Further, during the self-incompatibility response of Papaver rhoeas, destruction of the cytoskeleton is a primary target implicated in the rapid cessation of pollen tube growth and alterations in actin dynamics are associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
136
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(139 citation statements)
references
References 156 publications
3
136
0
Order By: Relevance
“…ABPs regulate F-actin polymerisation and organisation in plant cells 2 and are likely to have a role in mediating PCD. To date rather few ABPs have been examined in the context of PCD.…”
Section: How Is Regulation Of the Cytoskeleton To Mediate Pcd Achieved?mentioning
confidence: 99%
See 1 more Smart Citation
“…ABPs regulate F-actin polymerisation and organisation in plant cells 2 and are likely to have a role in mediating PCD. To date rather few ABPs have been examined in the context of PCD.…”
Section: How Is Regulation Of the Cytoskeleton To Mediate Pcd Achieved?mentioning
confidence: 99%
“…Alterations to the actin cytoskeleton are regulated by actin-binding proteins (ABPs) that stimulate formation of new filaments, promote filament elongation, bundle filaments together, strengthen interaction between actin/tubulin subunits, induce severing and depolymerisation. 2 Plant microtubules undergo dynamic instability 3 under the control of microtubule-associated proteins (MAPs; reviewed by Hamada 4 and Sedbrook 5 ). The dynamic nature of F-actin and microtubules enables flexibility of cytoskeletal organisation, making it an integral part of signalling networks, translating developmental and environmental cues into cellular responses.…”
mentioning
confidence: 99%
“…Furthermore, imaging of actin filaments has shown that distinct actin structures form in pollen tubes across different species. The consensus view is that actin filaments can be divided into at least three distinct structures in pollen tubes: longitudinal actin cables found in the shanks of pollen tubes; dense actin structures, such as collar-like structures or actin fringes, found at the subapexes; and highly dynamic, but less abundant, actin filaments found at the extreme tips (Kost et al, 1998;Fu et al, 2001;Lovy-Wheeler et al, 2005;Cheung et al, 2008;Chen et al, 2009;Vidali et al, 2009;Staiger et al, 2010). These distinct actin structures are believed to perform distinct functions.…”
Section: Introductionmentioning
confidence: 99%
“…Actin shapes and dynamics are modulated directly by several types of actin-binding proteins during pollen tube growth (Ren and Xiang, 2007;Staiger et al, 2010;Fu, 2015). In Arabidopsis and lily (Lilium longiflorum), fimbrins (FIM), domain of Lin11, Isl-1, and Mec-3 proteins, actin-depolymerizing factors, several formins, and villins (VLN) have been shown to be involved in the formation and maintenance of longitudinal actin cables in the shank region of pollen tubes Zheng et al, 2013;Fu, 2015).…”
mentioning
confidence: 99%